Knowledge, Attitudes, and Practices of Health Workers in Medical Waste Management During the COVID-19 Pandemic - I Gede Dedik Antara; I Gusti Ayu Rai Widowati; I Made Dharmadi; Putu Eka (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2024)
Medical waste (MW) has the potential to be hazardous due to the presence of dangerous microbes. During the COVID-19 pandemic, MW had exploded, particularly in healthcare facilities. The lack of knowledge, attitudes, and practices related to medical waste management (MWM) among health workers will have a substantial influence on public health and environmental health concerns. The objective of this research is to evaluate health workers' knowledge, attitudes, and practices encompassing MWM at the health center during the Covid-10 pandemic. This cross-sectional study was done from March to May 2023, involving direct interviews with healthcare workers at the Manggis I Karangasem Health Center. A total of 36 participants responded (100% response rate). The results demonstrate that the respondent's knowledge (n=34 [68.0%]) and attitude (n=44 [88.0%]) were considered good. Solid MWM practices in the emergency room (ER) were suitable (64.0%); liquid MWM in the ER were suitable (66.5%); solid MWM in polyclinic were suitable (64.0%); liquid MWM in polyclinic were suitable (83.0%); solid MWM in pharmacy were suitable (67.5%); liquid MWM in pharmacy were suitable(50.0%). In general, health workers' knowledge, attitudes, and practices in MWM were beneficial. Statutory requirements require periodic examinations of the necessity of handling medical waste in health facilities.